Synthesis and characterization of two series of non-symmetric liquid crystal dimer containing bisazobenzene moiety - Salisu, Abdulsalam Abubakar; Ab. Rahman, Mohamad Zaki; Silong, Sidik; Lutfor, Md Rahman; Ahmad, Mansor (Knowledgia Review, Malaysia, 2009)
Two series of calamitic non-symmetric liquid crystalline dimer compound containing bisazobenzene moiety and a rather short alkoxybiphenyl linked by flexible spacers 4-propyloxy-[4-biphenyloxyalkyl]-4`-(4-phenylazo)azobenzene has been synthesized and characterized by spectroscopic methods. The transition temperatures and phase behaviours were studied by Differential Scanning Calorimetry (DSC), Polarizing Optical Microscopy (POM) and X-Ray Diffraction (XRD) study. The synthesized compounds exhibited enantiotropic liquid crystal phase with dimer (D1) containing pentyl flexible alkyl spacer showing smectic A and smectic C phases and dimer (D2) with hexyl spacer exhibitig SmA and nemetic phases respectively and the stability of the smectic layer depends on the spacer length for the compounds studied.